Gentes de orden en espacios de desorden. El Resguardo de Rentas de la frontera de Extremadura con Portugal (1749-1788) - Miguel Ángel Melón Jiménez (Les Cahiers de Framespa)
Based on the documentation preserved in various files belonging to the Secretary and Superintendence of the Treasury of the General Archive of Simancas, a proposal is offered for an analysis of the dependents employed in the Revenue Guard who watched over the traffic of merchandise on the border between Spain and Portugal. On the basis of the correspondence, reform projects, reports, briefings and memoranda sent to the Ministry of Finance, the surveillance tasks entrusted to them will be studied, as well as the conditions in which they found themselves, the means at their disposal, their successes and failures against the fraudsters they pursued, and also their relations with their superiors in the chain of command, with the customs employees and with the local people.